267OTreatment outcome for gastric mucosa-associated lymphoid tissue lymphoma with Helicobacter Pylori negative. (24th November 2019) - Lim, S-N; Sohn, B S
Abstract: Background: Unlike that for Helicobacter pylori (H.pylori)-positive gastric mucosa-associated lymphoid tissue (MALT) lymphoma, the management strategy for H.pylori-negative MALT lymphoma remains controversial. Therefore, the aim of the present study was to examine the success of each treatment option for H.pylori-negative gastric MALT lymphomas. Methods: Between June 2000 and June 2017, a total of 89 H.pylori-negative gastric MALT lymphoma patients were enrolled retrospectively. H.pylori-positive status was defined by positive results for the biopsy urease test and histology. They had all been diagnosed by endoscopy and had a complete staging including CT-scan. Tumors that had resolved to complete remission score of GELA histologic grading system were considered treatment-responsive. Results: Sixty-two patients (69.7%) underwent H.pylori eradication therapy. After H.pylori eradication, ChR was achieved in 15 patients (24.2%) and pMRD in 13 (21.0%). he median time from H.pylori eradication to ChR or pMRD was 84 days. Fifteen patients took radiotherapy and six patients chose combination chemotherapy with or without rituximab as following, RCVP in 3, CVP in 1, and CHOP in 2. The all of them who took radiotherapy and chemotherapy achieved ChR. Median follow-up period was 45.4 months, lymphoma relapse was observed in nine patients (10.1%). Disease progression was observed in 3 of 33 non-responders. Probabilities of overall survival and event-free survival at 10 years were 98.5%, and 61.4%, respectively. Conclusions: A substantial proportion of patient with H.pylori-negative gastric MALT lymphoma remain antibiotic-responsive and can be cured using radiotherapy and chemotherapy. Legal entity responsible for the study: The authors. Funding: Has not received any funding. Disclosure: All authors have declared no conflicts of interest.